Fabrication of palm carotene-based emulsion stabilized by rice protein isolate-flaxseed gum complex - Choy, Hew Weng; Teow, Shuh Jun; Khor, Yih Phing; Tan, Tai Boon; Gholivand, Somayeh; Mat Yusoff, Masni; Tan, Chin Ping (Walter de Gruyter GmbH, 2024)
The aim of this study was to develop a stable palm carotene-based emulsion using the rice protein isolate-flaxseed gum complex (RPI-FG) with different ratios (3:1, 5:1, 7:1, 9:1, 11:1). RPI achieved highest solubility at pH 12. Meanwhile, RPI-FG complex shows low turbidity value from pH 6 to 12 for all ratios. Emulsion with ratio 7:1 exhibited 33% droplet size increment throughout 7 days storage and evenly distributed based on the microstructure images. For creaming index (CI), all emulsion shows 0% separation on day zero except emulsion with ratio 11:1 (1.90%) and lowest CI on day 7 was 9.05% in ratio 3:1. Furthermore, emulsion activity index and emulsion stability index of the emulsions decreased significantly with the reduced of FG in the formulation. These results suggested that carotene-based emulsion fabricated using RPI-FG complex with ratio of 7:1 exhibited the highest emulsion stability and could be further applied in aqueous food systems.